Case Report: A severe case of immunosuppressant-refractory immune checkpoint inhibitor-mediated colitis rescued by tofacitinib - Sweep, Mark W. D.; Tjan, Martijn J. H.; Gorris, Mark A. J.; Bol, Kalijn F.; Westdorp, Harm (Frontiers in Immunology, 2023)
Immune checkpoint inhibitor therapy for cancer treatment can give rise to a variety of adverse events. Here we report a male patient with metastatic melanoma who experienced life-threatening colitis and duodenitis following treatment with ipilimumab and nivolumab. The patient did not respond to the first three lines of immunosuppressive therapy (corticosteroids, infliximab, and vedolizumab), but recovered well after administration of tofacitinib, a JAK inhibitor. Cellular and transcriptional data on colon and duodenum biopsies shows significant inflammation in the tissue, characterized by a large number of CD8 T cells and high expression of PD-L1. While cellular numbers do decrease during three lines of immunosuppressive therapy, CD8 T cells remain relatively high in the epithelium, along with PD-L1 expression in the involved tissue and expression of colitis-associated genes, indicating an ongoing colitis at that moment. Despite all immunosuppressive treatments, the patient has an ongoing tumor response with no evidence of disease. Tofacitinib might be a good candidate to consider more often for ipilimumab/nivolumab-induced colitis.